Identifikasi Daerah Rawan Banjir di Kota Makassar - Himawan Sainul; Bambang Heryanto; Venny Veronica Natalia (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2014)
Floods are the events of the over flowing of water onto land. Floods often occurs in the Biringkanaya District of Makassar city. The research aim is to identify the flood vulnerability spot in Biringkanaya District using spatial analysis and calculation methods of rational water discharge and Darcy’s law. These methods are combined to identify the level of flooding vulnerability. The result shows that flood vulnerability spot in Biringkanaya District were located in every sub district which consists of a high, medium and low vulnerability state. The highest flood vulnerability is Paccerakkang and Sudiang Raya sub district.